2017
DOI: 10.3390/su9101917
|View full text |Cite
|
Sign up to set email alerts
|

Land-Surface Characteristics and Climate in West Africa: Models’ Biases and Impacts of Historical Anthropogenically-Induced Deforestation

Abstract: Land Use Land-Cover Change (LULCC), such as deforestation, affects the climate system and land-atmosphere interactions. Using simulations carried out within the LUCID (Land Use and Climate, IDentification of robust Impacts) project framework, we first quantify the role of historical land-cover change induced by human activities on surface climate in West Africa. Focusing on two contrasted African regions, we find that climate responses of land-use changes are small but they are still statistically significant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 77 publications
(103 reference statements)
1
21
0
Order By: Relevance
“…At global scale, projections of rainfall extremes are 2-2.5 times more dampened by future LCC than mean rainfall projections for at least two extreme indices (supplementary table S2, 'Global column' for PRCPTOT and R10mm versus P mean ). IPSL-CM5A-LR results clearly contrast with other model responses (figure 1, green triangle versus other symbols), as found in previous studies studying LCC/climate links (de Noblet-Ducoudré et al 2012, Pitman et al 2012, Sy et al 2017, Quesada et al 2017a. This model simulates local evapotranspiration increase in response to tropical deforestation (+0.60 W m −2 for IPSL-CM5A-LR latent heat flux changes above tropical deforested areas, i.e.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…At global scale, projections of rainfall extremes are 2-2.5 times more dampened by future LCC than mean rainfall projections for at least two extreme indices (supplementary table S2, 'Global column' for PRCPTOT and R10mm versus P mean ). IPSL-CM5A-LR results clearly contrast with other model responses (figure 1, green triangle versus other symbols), as found in previous studies studying LCC/climate links (de Noblet-Ducoudré et al 2012, Pitman et al 2012, Sy et al 2017, Quesada et al 2017a. This model simulates local evapotranspiration increase in response to tropical deforestation (+0.60 W m −2 for IPSL-CM5A-LR latent heat flux changes above tropical deforested areas, i.e.…”
Section: Discussionsupporting
confidence: 67%
“…areas with future decrease in tree fraction, versus −0.18, −1.71, −1.10 and −2.40 W m −2 for CanESM2, HadGEM2-ES, MPI-ESM-LR and MIROC-ESM, respectively). Such local negative evapotranspiration/tree cover tropical feedback is however not supported by observational data (Spracklen et al 2018) and to simulate it correctly is critical in projecting accurate mean and extreme rainfall responses to LCC (Sy et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This decline is significant at a 5% significance level. These differences between the north and the southeast can be explained by the strong land surface heterogeneities, the topography, and the remote response of local precipitation to changes in vegetation dynamics [25,26].…”
Section: Annual and Seasonal Changes Of Precipitation And Evapotranspmentioning
confidence: 99%
“…The annual water balance is represented in Figure 4. A general water deficit can be seen (more than 180 mm), which means that the water losses through the process of evapotranspiration are These differences between the north and the southeast can be explained by the strong land surface heterogeneities, the topography, and the remote response of local precipitation to changes in vegetation dynamics [25,26].…”
Section: Annual and Seasonal Changes Of The Water Balance (P-et)mentioning
confidence: 99%
“…Pellarin [110] reached a similar conclusion and observed that the initiation, but also the path and behavior of MCS appear to be influenced by the soil moisture patterns during daytime, their path evolving preferentially on the edge of wet areas. Sy et al (2017) [111] showed that, although climate responses to land use changes seem to be relatively small, some atmospheric processes are influenced by LULCC.…”
Section: Main Trends Described In Recent Workmentioning
confidence: 99%